The Antisteatotic and Hypolipidemic Effect of Insect Meal in Obese Zucker Rats is Accompanied by Profound Changes in Hepatic Phospholipid and 1‐Carbon Metabolism. Issue 8 (1st February 2019) - Meyer, Sandra; Gessner, Denise K.; Wen, Gaiping; Most, Erika; Liebisch, Gerhard; Zorn, Holger; Ringseis, Robert; Eder, Klaus
Abstract : Scope: The hypothesis is tested that insect meal, which has a low methionine content, reduces the hepatic phosphatidylcholine (PC):phosphatidylethanolamine (PE) ratio, which is a critical determinant of hepatic lipid synthesis, by decreasing availability of the methionine metabolite S‐adenosylmethionine (SAM). Methods and results: Obese rats ( n = 24) are randomly divided into two groups (Obese Casein and Obese Insect) of 12 rats each. In addition, lean rats ( n = 12) are used as control group (LC). Groups LC and OC receive a control diet with casein as protein source, whereas in the OI group, casein is replaced isonitrogenously by insect meal, which is found to be less digestible (–12% units). Plasma and liver concentrations of lipids and hepatic expression of lipid synthesizing genes are reduced in the OI group compared to the OC group. Plasma and liver concentration of PC and the PC:PE ratio are decreased in the OI group compared to the OC group, while hepatic concentration of SAM and the hepatic SAM:S‐adenosylhomocysteine (SAH) ratio is lower in the OI group than in the OC group. Conclusion: The decrease of the hepatic PC:PE ratio is probably a key mechanism explaining the pronounced antisteatotic and hypolipidemic action of insect meal in obese rats. Abstract : Insect meal, which has a low methionine content, reduces the hepatic phosphatidylcholine (PC)/phosphatidylethanolamine (PE) ratio, a critical determinant of hepatic lipid synthesis, by decreasing availability of the methionine metabolite S‐adenosylmethionine (SAM). The decrease of the hepatic PC/PE ratio is probably a key mechanism explaining the pronounced antisteatotic and hypolipidemic action of insect meal in obese rats.